Deciphering the dynamics of a Younger Dryas rock avalanche in the Bernese Alps - Giacomina Bucher; Catharina Dieleman; Susan Ivy-Ochs; Jordan Aaron; Christof Vockenhuber; Naki Akçar (Swiss Journal of Geosciences)
Abstract Large rock avalanches play a key role in shaping alpine landscapes. However, the complex interplay between mass movement and other surface processes poses challenges in identifying these deposits and understanding the underlying process controls. Here, we focus on the rock avalanche deposit of the Lurnigalp valley in the Bernese Alps (Switzerland), originally mapped as till. The Lurnigalp valley is a U-shaped tributary valley located in the southwest of Adelboden, Canton Bern. To explore the timing and dynamics of the rock avalanche event, we employed detailed remote and field mapping, sedimentary petrology, surface exposure dating with cosmogenic 36Cl, and runout modelling with DAN3D®. For the reconstruction of the chronology, we analyzed cosmogenic 36Cl in surface samples from 15 boulders of the rock avalanche deposit. We developed three distinct scenarios to investigate the dynamics and contextual conditions of the rock avalanche event. In the first scenario, we consider a rock avalanche depositing 1 Mm3 of sediment in a valley devoid of ice. The second scenario uses the same deposit volume but introduces a hypothetical glacier occupying the uppermost part of the valley. Finally, the third scenario, similar to the first scenario with a glacier-free valley, assumes a substantially larger volume of collapsed rock mass. We consider the third scenario the most plausible, in which approximately 6 Mm3 of rock mass, composed of limestone and sandstone, was released from a limestone cliff around 12 ± 2 ka during the Younger Dryas. The collapsed rock mass fell into the ice-free valley floor, ran up the opposite valley side and was deflected towards the northeast following the valley orientation. The rock mass stopped after 2.2 km leaving approximately 6.4 Mm3 deposits spread across the entire valley floor. Subsequently, most of the rock avalanche deposit have been reworked by periglacial activity. We suggest that structural features, lithology and glacial erosion and debuttressing were involved in the weakening of the in-situ bedrock that finally led to the collapse. Our study not only enhances the understanding of rock avalanche mechanisms and their profound impact on Alpine landscape evolution but also elucidates the complex interplay of geological processes that led to the collapse and altered the rock avalanche deposit afterwards.